Association between relative liver enhancement on gadoxetic acid enhanced magnetic resonance images and histologic grade of hepatocellular carcinoma. Issue 30 (July 2017) - Jin, Young-Joo; Cho, Soon Gu; Lee, Kun Young; Kim, Joon Mee; Lee, Jin Woo
Abstract : Abstract: We evaluated the association between histologic grade of hepatocellular carcinoma (HCC) and degree of HCC enhancement on Gd-EOB-DTPA (Gadoxetic acid, Primovist)-enhanced magnetic resonance images (MRI) in HCC patients. A total of 121 patients who underwent curative surgical resection for HCC at our institution between January 2012 and March 2015 were retrospectively analyzed. Gadoxetic acid enhanced MRI was performed in all patients before surgery. Signal intensities of HCC and peri-HCC areas were measured using regions of interest. Relative intensity ratios of HCC lesions versus the surrounding non-HCC areas on unenhanced images (precontrast ratio) and on hepatobiliary phase images (postcontrast ratio) were calculated. Relative liver enhancement (RLE) ratios (post-contrast ratio/pre-contrast ratio) were also calculated. The Edmondson–Steiner (E-S) grading system was used to histologically grade HCC. E-S grades I, II, III, and IV were observed in 2 (1.7%), 14 (11.6%), 54 (44.6%), and 51 (42.1%) of the patients, respectively. For E-S grades I/II (n = 16), III (n = 54), and IV (n = 51), mean RLE (%) were 85.5, 84.9, and 71.2, respectively ( P  = .01), and for E-S grades I-III (n = 70) and IV (n = 51), mean RLE (%) were 85.1 and 71.2, respectively ( P  < .01). Barcelona Clinic Liver Cancer (BCLC) stage A (vs 0) (odds ratio 4.38, P  = .03) and mean RLE (odds ratio 0.05, P  < .01) were found to predict E-S grade IV. E-S grade IV was associated with a low level mean RLE in the gadoxetic acid enhanced MR images of HCC patients.